2013
DOI: 10.1007/s00705-013-1838-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in the leader and P1-coding regions of foot-and-mouth disease virus serotypes A and O in Africa

Abstract: Genetic information regarding the leader (L) and complete capsid-coding (P1) region of FMD serotype A and O viruses prevalent on the African continent is lacking. Here, we present the complete L-P1 sequences for eight serotype A and nine serotype O viruses recovered from FMDV outbreaks in East and West Africa over the last 33 years. Phylogenetic analysis of the P1 and capsid-coding regions revealed that the African isolates grouped according to serotype, and certain clusters were indicative of transboundary as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 80 publications
(106 reference statements)
2
14
0
1
Order By: Relevance
“…Recombination events are rarely observed in the capsid proteins (46), and are more frequently observed in the nonstructural coding regions (105). Studies with field isolates have also reported these observations through the analysis of WGS, confirming these observations with several serotypes, including A and Asia 1 (18,40,60), and reconfirming that the non-structural regions are more likely to be involved in recombination events, particularly in regions where cocirculation of the multiple serotypes and/or topotypes is present.…”
Section: Genomics As a Tool For Understanding Viral Evolution: Viral mentioning
confidence: 56%
See 1 more Smart Citation
“…Recombination events are rarely observed in the capsid proteins (46), and are more frequently observed in the nonstructural coding regions (105). Studies with field isolates have also reported these observations through the analysis of WGS, confirming these observations with several serotypes, including A and Asia 1 (18,40,60), and reconfirming that the non-structural regions are more likely to be involved in recombination events, particularly in regions where cocirculation of the multiple serotypes and/or topotypes is present.…”
Section: Genomics As a Tool For Understanding Viral Evolution: Viral mentioning
confidence: 56%
“…One of the most important applications for FMDV nucleotide sequence data has been in the field of molecular epidemiology (7), where phylogenetic comparisons of VP1 sequence data are widely and routinely used to monitor outbreaks (13,14,15,16). Although VP1 has become the most commonly used and robust genetic marker for outbreak tracing, other studies have also focused on the phylogenetic analysis of other FMDV genomic regions (17,18,19). Phylogenetic analysis of VP1 can be applied to categorise field strains into discrete topotypes and lineages which, despite the tendency for the virus to spread, frequently show geographical clustering based on the historical distribution of the virus (20).…”
Section: Molecular Epidemiology Using Partial Genome Sequencesmentioning
confidence: 99%
“…2) except for VP2 134. [14]. The coloration represents topotype-specific sites in the axes of viral surfaces.…”
Section: Analysis Of Antigenic Sites Among East Asian Isolates and Vamentioning
confidence: 99%
“…The VP1 with antigenic site 1 (twofold axis, 135-163 amino acids [aa]), site 2 (threefold axis, 193-213 aa), and site 4 (fivefold axis, 167-178 aa); VP2 with antigenic site 3 (twofold axis, 79-88 aa; threefold axis, 188-198 aa); and VP3 with antigenic site 5 (threefold axis, 58-72 aa) and site 3 (threefold axis, 132-142 aa) were analyzed for similarity rates with the full amino acid sequence of each structural viral protein [14].…”
Section: Sequence Data and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation